2018
DOI: 10.1007/s40273-018-0678-6
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation for USA of Systemic Chemotherapies as First-Line Treatment of Metastatic Pancreatic Cancer

Abstract: This sponsor-independent economic evaluation for USA found that OX + GEM, CAP + GEM, FOLFIRINOX, and NAB-P + GEM, but not CIS + GEM, were more expensive but also more effective than GEM alone in terms of quality-adjusted life-years and life-years gained. The NAB-P + GEM regimen appears to be the most cost effective in USA at a willingness-to-pay threshold of US$200,000/quality-adjusted life-year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…A Markov model was developed to estimate the costs and treatment efficacy of metastatic pancreatic cancer and takes olaparib as a maintenance therapy compared with placebo within three mutually exclusive health states (Figure 1): "progression-free survival (PFS)" (initial state of patient until progression), "progression survival (PS)" (state after disease progression), and "death" (absorption state) (Gharaibeh et al, 2018). All patients entered the model from the PFS state; they could then either survive the PFS state or enter the PS state.…”
Section: Methods Model Structurementioning
confidence: 99%
See 1 more Smart Citation
“…A Markov model was developed to estimate the costs and treatment efficacy of metastatic pancreatic cancer and takes olaparib as a maintenance therapy compared with placebo within three mutually exclusive health states (Figure 1): "progression-free survival (PFS)" (initial state of patient until progression), "progression survival (PS)" (state after disease progression), and "death" (absorption state) (Gharaibeh et al, 2018). All patients entered the model from the PFS state; they could then either survive the PFS state or enter the PS state.…”
Section: Methods Model Structurementioning
confidence: 99%
“…BSC and terminal care are necessary in all strategies because of the lack of ideal replacement therapies and the high mortality of metastatic pancreatic cancer (Wu et al, 2014;Gharaibeh et al, 2018). After progression, the cost of BSC was the only cost included in the analyses.…”
Section: Cost Estimatesmentioning
confidence: 99%
“…31,32 However, there is a dearth of information regarding the economic outcome of maintenance treatments for MPC. Although 2 previous economic analyses have shown that a chemotherapy regimen containing nab-paclitaxel was cost-effective in the United States and United Kingdom, 20,33,34 these analyses included treatment-naïve patients with MPC. The target populations in those studies were different from ours in that the patients we studied had received at least 16 weeks of continuous first-line platinum-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The results were most sensitive to changes in AE management cost, base-case utility associated with PD, and utility of pancreatic cancer studies are lower than our estimates. 17,18 The reason our effectiveness estimates are higher could be due to the study population.…”
Section: Sensitivity Analysismentioning
confidence: 93%
“…Costs associated with acquiring and administering chemotherapy treatments, basic supportive care, inpatient, outpatient, pharmacy, and managing AEs were used to calculate the total costs associated with FOLFIRINOX and GemNab. [16][17][18][19] These costs were obtained from Kim et al, 16 who performed a retrospective analysis of hospital claims The effect of our assumptions on input parameters was explored with sensitivity analysis. One-way sensitivity analysis was conducted to determine the robustness of the model and to explore the influence of key input parameters.…”
Section: Model Assumptionsmentioning
confidence: 99%